Variations in prevalence rates of tick-borne diseases in Zebu cattle by agroecological zone: Implications for East Coast fever immunization - Deem, S.L.; Perry, Brian D.; Katende, J.M.; McDermott, John J.; Mahan, S.M.; Maloo, S.H.; Morzaria, S.P.; Musoke, A.J.; Rowlands, G.J. (Elsevier, 1993)
East Coast fever (ECF), caused by Theileria parva, is the most important tick-borne disease of cattle in much of eastern, central and southern Africa. In Kenya, immunization against ECF has been performed in many field trials using the infection and treatment method. The main targets for immunization are the Taurine and Taurine-cross cattle, due to their high susceptibility. However, indigenous Zebu cattle may also be targets for immunization where endemic instability to this parasite exists. For both cattle types, it's important to know the prevalence of other tick-borne diseases if the frequency of acaricide application is to be reduced flowing ECF immunization. In the coast province of Kenya there are four district agroecological zones (AEZs), classified on agroclimatic factors. The environmental conditions in these AEZs vary in their suitability for Rhipicephalus appendiculatus, the main field vector of ECF. The abundance of this tick has a direct impact on the degree of endemic stability to T. parva and is hence the justification for immunization in the predominantly Zebu cattle population of the province. A serological study was conducted on 316 Zebu calves on 30 farms in three of the four agroecological zones, and prevalence rates to Theileria parva, T. mutans, Babesia bigemina, Anaplasma marginale and Cowdria ruminantium were determined. Antibody prevalence rates to T. parva differed across AEZs whereas to the other tick-borne diseases they were uniformly high. It is concluded that the justification for immunization of Zebu cattle against ECF varies with AEZ, and that any reduction in acaricide usage following immunization is unlikely to be accompanied by an increased incidence of other tick-borne diseases. The sampling methodology used in the study was evaluated for its precision, and recommendations for sampling strategy in future studies of tick-borne disease prevalence are made.